PENGARUH PENERAPAN HANDOUT FISIKA BERORIENTASI MODEL PEMBELAJARAN PEMECAHAN MASALAH KREATIF TERHADAP PENCAPAIAN KOMPETENSI SISWA KELAS X SMA NEGERI 8 PADANG - Suharyadi Suharyadi; Djusmaini Djamas; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2016)
This research is motivated by the lack of competency of students. Therefore, researchers tried a handout Physics oriented learning model of Creative Problem Solving is expected to develop students' creativity in solving problems of learning and encourage students to present ideas that will increase student competence. The purpose of research is to investigate the effect of the application-oriented learning model handout Physics Creative Problem Solving towards the attainment of students of class X SMAN 8 Padang. Type of research is quasi experimental design with Randomized Control Group Only Design. The study population is all students of grade X SMAN 8 Padang enrolled in the Academic Year 2015/2016. Taking of sampling was done by using purposive sampling technique. The sample which present in this research is class X.8 as an experimental of class and class X.9 as the control of class. The research data covers three competencies where are competence of knowledge, attitude competence, and competence skills. The research instrument is achievement test for competency knowledge, observation sheets attitude for attitude competence, and competence assessment rubrics for skills. Data were analyzed by testing the equality of two average and regression and correlation. Equality test performed on average two to the value of the learning outcomes of each competency second grade sample. Regression and correlation do to the value of learning outcomes competences experimental class knowledge.Based on the analysis of data obtained by the average value for the experimental class and the control class in a row on the competence of knowledge, namely 82.96 and 72.75, on the attitude of competence, namely 78.76 and 72.46, and the competencies and skills that 83.86 78.58. Data for the competence of knowledge, attitudes, and skills of both classes of normally distributed samples and having variances were homogeneous, so do test the equality of two average by t-test. From the calculation results obtained tcount 3.10 competencies for the knowledge, competencies, namely 2,804 attitudes, skills and competence is 2.275 with a value table = 1.669. Percentage influence handout Creative Problem Solving Physics oriented towards the attainment of Physics students at 33.40%. So it can be concluded that the application of Physics handout oriented Creative Problem Solving learning model can improve student achievement of competence Physics Class X SMAN 8 Padang